Case Report: Complete pathological remission of human chorionic gonadotrophin-producing gallbladder carcinoma with multiple liver metastases after treatment with chemotherapy plus an immune checkpoint inhibitor - Wang, Qianwen; Mu, Yunchuan; Ji, Shunxian; Liu, Yang; Lou, Yanbo; Wei, Shumei; Dong, Xin; Zhang, Bo (Frontiers in Immunology, 2023)
Background Gallbladder carcinoma (GBC) producing human chorionic gonadotrophin (HCG) is an extremely rare and highly invasive tumor with a poor prognosis. This unfavorable clinical outcome is partly due to the aggressive nature of the tumor and its insensitivity to chemotherapy. Case presentation We herein report a case of primary GBC producing HCG with liver metastases in a 58-year-old woman. The patient presented with a markedly elevated β-HCG level and a mass in the gallbladder with multiple liver metastases. A definitive diagnosis was obtained after a needle biopsy of the liver metastases, showing poorly differentiated carcinoma with large-scale necrosis and strong positivity of immunostaining for HCG in tumor cells. The patient received chemotherapy (gemcitabine plus capecitabine) combined with carrellizumab, an immune checkpoint inhibitor (ICI). Pathological complete response was achieved after eight courses of combined therapy, which was confirmed by pathological analysis of resected specimens. After surgery, two courses of chemotherapy plus ICIs were adopted again. Complete response remained for approximately 1 year up to the present. Tumor tissue was collected to perform immunostaining of PD-L1, whole-exome sequencing, and RNA-seq. Low-TMB (1.51 mut/Mb), MSS, and high PD-L1 expression (TPS ≥ 50%) were observed in the tumor. Besides, the dominant types of infiltrating immune cells were macrophage and CD4+ T cells. Compared to other gallbladder adenocarcinoma without HCG, the proportion of M1 macrophage was at a higher level and the gene sets of MYC targets v1 and PI3K/AKT/mTOR signaling were highly expressed in our case. To the best of our knowledge, this is the first case report of complete remission of HCG-producing gallbladder carcinoma with liver metastases after chemotherapy combined with an immune checkpoint inhibitor. Furthermore, this is also the first report that described the tumor genetic feature and tumor immune microenvironment atlas of HCG-producing GBC. Conclusion chemotherapy plus an immune checkpoint inhibitor may provide a potentially curative option for gallbladder carcinoma with HCG production.